Evolutionary frequency response function of linear systems subjected to earthquake accelerograms using the adaptive chirplet decomposition. (2017) - Alderucci, T.; Giunta, F.; Muscolino, G.
Abstract: In seismic engineering, in order to reproduce the typical characteristics of real earthquakes ground-motion time history, several approaches has been proposed in literature. In this study the adaptive chirplet signal decomposition is adopted to analyze recorded accelerograms in order of defining appropriately evolutionary power spectra [1]. The present study focuses on a method to evaluate in closed-form the evolutionary frequency response function, that is required to evaluate the statistics of the response of linear structural systems [2], once the adaptive chirplet signal decomposition is adopted.